Comparative study of 18F-DCFPyL PET/CT and 99mTc-MDP SPECT/CT bone imaging for the detection of bone metastases in prostate cancer - Hu, Xiongjian; Cao, Yiming; Ji, Bin; Zhao, Min; Wen, Qiang; Chen, Bin (Frontiers in Medicine, 2023)
Purpose This study aimed to compare the diagnostic efficiency of 18F-DCFPyL PET/CT imaging and 99mTc-MDP SPECT/CT bone imaging for the detection of bone metastases in prostate cancer. Methods A retrospective analysis was conducted on 31 patients with confirmed prostate cancer between September 2020 and September 2022 at China-Japan Union Hospital of Jilin University. All patients underwent 18F-DCFPyL PET/CT and 99mTc-MDP SPECT/CT bone imaging. The gold standard was the pathology or Best Valuable Comparator (BVC) result based on clinical follow-up. Diagnostic performance indicators, including sensitivity, specificity, accuracy, positive predictive value (PPV), and negative predictive value (NPV), were analyzed at both the patient and lesion levels. The paired sample chi-square test was used to compare the two imaging methods. Receiver operating characteristic (ROC) curves were plotted, and the area under the curve (AUC) was calculated for each method. The AUC values were compared using the Z-test, and a p-value < 0.05 was considered statistically significant. Results Of the 31 prostate cancer patients, 18 were diagnosed with bone metastases, with a total of 84 bone metastatic lesions. At the patient level, 18F-DCFPyL PET/CT imaging showed superior diagnostic performance compared to 99mTc-MDP SPECT/CT bone imaging in all indicators: sensitivity (100% vs. 77.8%, p < 0.01), specificity (92.3% vs. 69.2%, p < 0.05), accuracy (96.8% vs. 74.2%, p < 0.01), PPV (94.7% vs. 77.8%, p < 0.01), and NPV (100% vs. 69.2%, p < 0.01). The AUC values for 18F-DCFPyL PET/CT imaging and 99mTc-MDP SPECT/CT bone imaging were 0.962 and 0.735 (Z = 2.168, p < 0.05). At the lesion level, 18F-DCFPyL PET/CT imaging showed superior diagnostic performance compared to 99mTc-MDP SPECT/CT bone imaging in all indicators: sensitivity (97.6% vs. 72.6%, p < 0.01), specificity (95.7% vs. 73.9%, p < 0.01), accuracy (97.2% vs. 72.9%, p < 0.01), PPV (98.8% vs. 91.0%, p < 0.01), and NPV (91.7% vs. 42.5%, p < 0.01). The AUC values for 18F-DCFPyL PET/CT imaging and 99mTc-MDP SPECT/CT bone imaging were 0.966 and 0.733 (Z = 3.541, p < 0.001). Conclusion Compared with 99mTc-MDP SPECT/CT bone imaging, 18F-DCFPyL PET/CT imaging demonstrated higher diagnostic efficiency for bone metastases in prostate cancer, and it can more accurately determine the presence of bone metastases. It is an important supplement to imaging examination for prostate cancer patients and has great potential and broad application prospects.